La información para la empresa y el sistema de i+d+i: el caso de la región valenciana - Muñoz Cañavate, Antonio (Revista General de Información y Documentación, 2009)
Not only has the field of corporate information management been almost entirely neglected in Spain's LIS curricula and had hardly any echo in its LIS research, but there is widespread unawareness of the job opportunities that it represents. Nonetheless, the acceptance by the business and economics world of information as a resource of prime importance has led to the emergence of the discipline of Competitive Intelligence aimed at resolving the problems of information, and reducing the uncertainty that companies often find themselves surrounded by. After a brief description of the Spanish system of Science, Technology and Society, and of the corporate structure and enterprise culture of Valencia, the work focuses on two of the axes of the R & D & I support system of the Valencia Autonomous Community through its information systems for companies: the Regional agency for the promotion of innovation, Impiva, and the Region's network of technology centres. These structures are seen to provide support for the decision-making process on issues that affect many different corporate departments.
Keywords: Information; Corporations; R & D & I system; Spain; The Valencia Autonomous Community